Gender differences in nutritional intake and status in healthy free-living elderly - Kusumaratna, Rina K. (Universa Medicina, 2008)
Malnourishment in the older population is reported to be a consequence of inadequate food intake, underlying diseases, with females being at higher risk and economically more vulnerable. The objective of this study were to determine the patterns of gender differences in nutritional intake and status among free-living elderly in the Jakarta urban area. A cross sectional design was performed on free-living elderly people aged 60 years and older in South Jakarta. A total of 298 free-living elderly were interviewed on demography and social economic status, and assessed on anthropometric measures, two-day nonconsecutive dietary recall and biochemical indices using fasting blood samples. This study showed that most significant gender differences were in daily energy and nutrient intakes. Males had more energy intake 1246.6 kcal compared to female 1043.1 kcal and consumed more carbohydrate 168.1 g, protein 39.7 g, total vitamin A 12229.7 mg, vitamin C 22.3 mg, iron 6.87 mg, and zinc 4.9 mg food sources. Older males had better status indices for anemia than did older females (p=0.009). Older persons who co-resided with family had better dietary nutrient intakes than those living in nuclear families, except for protein, total vitamin A and zinc food sources. There are gender differences in energy, dietary nutrient intake, nutritional status and health status in free-living elderly. Both genders were deficient in all macronutrients and selected micronutrients, especially iron and zinc.